Cancer journeys and health practitioners as gatekeepers, brokers, and boundary enforcers - Dew K; Chamberlain K; Egan R; Dennett E; Cunningham C (SAGE Publications, 2026)
Cancer survival is increasingly prevalent, and the longevity of survivors enable them to provide insights into the experiences of living with cancer. The objective of this article is to consider the roles that health practitioners play that can facilitate or provide hindrances to investigations and cancer treatment following a diagnosis of cancer. From 2020 to 2022, 81 interviews were conducted with Māori and non-Māori throughout Aotearoa New Zealand identified as having survived cancer for a long time, from 4 to 37 years. Three primary roles were identified from the participants’ stories: practitioners as gatekeepers, brokers, and boundary enforcers. We suggest that each of these roles is based on different forms of integrity: professional, personal, and scientific. Findings raise concerns about the potential for the healthcare system to foster iniquitous outcomes and to marginalise those who explore alternative understandings of cancer and its treatment. To better support survivorship the healthcare system could be more expansive in its approach, improve its performance in the capacity to detect cancer signals, particularly in patients with a prior history of disease, and take a more tailored approach to cancer survivorship.
Keywords: cancer survivorship; inequity; incommensurability; delays in diagnosis; differential treatment; gatekeepers; boundaries